First Newsletter of the CGIAR Initiative on Agroecology [September 2022] - Quintero, Marcela; Wiederkehr Guerra, Gabriela Patricia; Staiger Rivas, Simone; Dickens, Chris (2022)
Agroecology shows enormous potential for helping address these crises, and the time has come for more concerted action to realize its possibilities. We thank you for having expressed interest in receiving this newsletter from the CGIAR Initiative on Agroecology. In this first edition we provide an overview of the Initiative, our set off webinar, and latest updates on partnerships, events, and publications.